M140. WHAT HAPPENS IN THE BRAIN A FEW SECONDS BEFORE THE ONSET AND OFFSET OF AN HALLUCINATORY EPISODE?. (18th May 2020) - Craven, Alexander; Ersland, Lars; Stoyanov, Drozdstoy; Kandilarova, Sevdalina; Sommer, Iris; Johnsen, Erik; Hugdahl, Kenneth
Abstract: Background: Auditory verbal hallucinations (AVH), the sense of "hearing voices" in the absence of a corresponding auditory source, are a major symptom in schizophrenia. Hemodynamic and electrophysiology studies have shown aberrant activation in fronto-temporal speech and language areas (Curcic-Blake et al., 2017 for review) – indicating neurobiological mediators relating to onset and duration of AVH episodes. However, unanswered is the question of specific neuronal precursors to the spontaneous cessation of an AVH episode. We therefore studied what happens in the brain a few seconds before both the onset and offset of an AVH episode. Methods: Structural and functional MRI data were collected from 44 patients diagnosed with a schizophrenia spectrum disorder, at three sites (University of Bergen, Norway, n=12; Medical University of Plovdiv, Bulgaria, n=13; Utrecht University Medical Center, Netherlands, n=19, total 25m, 19f, age 37.9+/-13.2 years). Symptom severity was assessed with the PANSS; mean total (+/-SD) 64.9+/-16.9; P3 hallucinatory behaviour 4.6+/-1.1. Additional assessments (not reported), scanner hardware and particulars of the MR acquisition varied between sites. Functional data were collected with a "symptom-capture" paradigm (Sommer et al., 2008), where subjects were instructed to press a button when a hallucinatory episode began, and another when the episode ended. Functional data were processed using an FSL FEAT pipeline, with additional filtering using the ICA_AROMA method. Data were then subjected to statistical analysis, contrasting hallucinatory with non-hallucinatory periods; higher-level analysis allowed comparison with findings from previous meta-analyses (Kompus et al. 2011, Jardri et al., 2011). A number of regions of interest were selected based on an initial PCA, in addition to regions nominated in the meta-analyses. For each region, for each start- and end-of-hallucination event, a time-course was extracted for the interval t=-10 to +15sec with respect to button-press onset. Time-courses were aligned and group-averaged (rejecting outliers iteratively) to yield a model time-course for start- and end- hallucinatory events in each region. Permutation analysis (n=5000) was performed to identify differential effects between start and end events. Results: Functional block-analysis revealed several clusters of activation, including among others the left fronto-temporal language areas (superior temporal gyrus and Broca's area). Similar patterns were present on a per-site basis. Time-course analysis demonstrated a differential effect in the left paracingulate sulcus, characterized by a significant dip in activation (Δ=-158iu, p=0.021) at the end-of-hallucination events, in contrast to a significant peak (Δ=35iu, p=0.0142) at the start-of-hallucination events. This activity preceded the motor response for the same events. Discussion: Clusters identified in the block-analysis at group-level were consistent with findings from meta-analyses; this attests to the validity of the source data and initial processing. The novel finding of anticipatory neuronal activity in the paracingulate region, differentiated between onset and offset of AVH- events, complements recent findings of reduced functional connectivity (Alonso-Solís et al., 2015) and morphological differences (Garrison et al., 2019) in the same region. This suggests that the paracingulate region may be crucial in both the initiation and the cessation of an AVH-episode and speaks to a kind of regulatory role for the region. This may in turn point to differential action of excitatory and inhibitory transmitters at a lower level of explanation.